Comparative evaluation of toxicology and sociodemographic characteristics in homicide and suicide victims - Bogdanović, Milenko; Babić, Miloš D.; Janković, Dušan; Radnić, Bojana; Aćimović, Tijana; Alempijević, Djordje; Pavlekić, Snežana (Vojnosanitetski pregled, 2023)
Background/Aim. Suicide and homicide are crucial social problems, especially frequent among the population younger than 40 years. The aim of this study was to assess the influence of different sociodemographic factors and relevant psychoactive substances on the difference between homicide and suicide victims. Methods. A cross-sectional study analyzed autopsy reports of 714 suicide and 166 homicide cases autopsied in five years (2011–2016). Out of these, 666 suicide and 127 homicide cases met the inclusion criteria for this study. Blood-ethanol concentration was determined by headspace gas chromatography with flame ionization detection. Analysis of substances other than ethanol was accomplished by gas chromatography-mass spectrometry and liquid chromatography with tandem mass spectrometry. Results. There was a significant difference in age, level of education, and employment rate between suicide and homicide cases (p < 0.05). The distribution of suicide and homicide cases differed significantly on weekdays compared to weekends [odds ratio(OR) = 1.5; 95 % confidence interval (CI) = 1–2.3; p < 0.05]. The presence of a psychoactive substance remained a nonsignificant predictor of whether a person would become a homicide or suicide victim (p > 0.05). Homicide victims were more likely to have significantly higher blood alcohol concentration (0.2–0.3 g/dL) than suicide victims (OR = 2.2; 95 % CI = 1–5; p < 0.05). Conclusion. The age, level of education, employment status, and high blood alcohol concentration (0.2–0.3 g/dL) of the victim were significantly different between suicide and homicide cases.